2016
DOI: 10.1016/j.gca.2016.04.042
|View full text |Cite
|
Sign up to set email alerts
|

Ahrensite, γ-Fe2SiO4, a new shock-metamorphic mineral from the Tissint meteorite: Implications for the Tissint shock event on Mars

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain. where it forms through the transformation of the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
56
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(60 citation statements)
references
References 60 publications
4
56
0
Order By: Relevance
“…() and Ma et al. () demonstrated that ringwoodite is actually composed of 0.05–0.4 μm grains. Additionally, the aggregation and preservation of original zoning in ringwoodite suggest that solid‐state transformation is likely the main mechanism for ringwoodite formation in Tissint (Walton et al.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…() and Ma et al. () demonstrated that ringwoodite is actually composed of 0.05–0.4 μm grains. Additionally, the aggregation and preservation of original zoning in ringwoodite suggest that solid‐state transformation is likely the main mechanism for ringwoodite formation in Tissint (Walton et al.…”
Section: Introductionmentioning
confidence: 96%
“…; Ma et al. ). Such a process is rapid and would occur on a time scale of tens of nano‐seconds (Tschauner et al.…”
Section: Introductionmentioning
confidence: 98%
“…These localized ‘hotspots' occur at locations of low-shock impedance where a larger fraction of shock energy is converted to heat rather than compression. Sources of hotspot formation include frictional heating between minerals of different impedances, collapse of voids or fluid inclusions or breakdown of hydrous minerals upon shock4246. Whitlockite/merrillite has a lower shock impedance than the major rock-forming minerals in meteorites20.…”
mentioning
confidence: 99%
“…In order to confirm their hypothesis, more investigation should be conducted on the meteoritic Rw, which represents the best natural specimen for studying high-P structural features, including the Mg-Si order-disorder state, due to its having much larger quench rates. Rw of various colors has been documented in many meteorites, including L ordinary chondrites [108][109][110][111][112], LL ordinary chondrites [14,26], and Martian meteorites like the shergottites [32,34,37]. If the relationship among the color, composition, inverse magnitude, P and T can be adequately quantified, a fine scale for accurately estimating the shock P-T conditions may be derived, which may serve well the theoretical evolution models of the early solar system.…”
Section: Discussionmentioning
confidence: 99%